Effect of Physical Activity on Depression and Psychological Well-Being - İsmail Koç and Rıdvan Ergin (Journal of Educational Issues, 2024)
Aim: This research was conducted to determine whether physical activity had an effect on the levels of depression and psychological well-being. Material and Method: In this research, the single group pre-test post-test model which is one of the trial models was used for the purpose of determining the causal relationship. The study group is composed of 43 sedentary volunteer students (nMales = 9, nFemales = 34; age 20.86±1.04 years) pursuing their education at the Emergency Medical Technician Program in the Vocational School of Health Services at the Kırşehir Ahi Evran University. The heights and body weights of the study group are measured and they are asked to fill out the “Personal Identification Form”. The 10-week physical activity program was explained to the students. For the purpose of determining their levels of depression before and after the physical activity, the “Beck Depression Inventory (BDI)” was used, and to measure their psychological development, the “Psychological Well-Being Scale (PWBS)” was used. The descriptive statistics were provided. Later on, the normality assumption was checked out. In the consequence of this assumption, the researcher decided to conduct the Wilcoxon Signed Ranks Test. The data is tested at the level of significance of α = 0.05. The researcher obtained permission from both the related institution and the ethical board. Results: The BDI pre-test results of the students indicate that the male students had minimal level of depression (0-9) and the female students had slight level of depression (10-16). In terms of the study group, while the students were found to have slight level of depression in terms of their BDI pre-test scores, it was observed that the students had minimal level of depression in terms of their post-test scores. At the same time, the scores of the pre-test and post-test PWBS score increased from 49.89 to 53.33 for males, and from 41.94 to 43.94 for females. In sum, those scores increased from 43.60 to 45.91. A significant difference (p < 0.05) in both BDI and PWBS between the pre-test and post-test was observed. While the depression levels of the students decreased, their psychological well-being levels increased. Conclusion and Suggestions: The 10-week physical activity program caused an improvement both at the levels of depression and psychological well-being. Therefore, sparing some time for physical activity is suggested for our psychological health on a daily basis. Do not forget: “physical activity is going to benefit people”.